PENANGGULANGAN PENYALAHGUNAAN NARKOTIKA MELALUI PENEGAKAN HUKUM DAN KESADARAN BERAGAMA DI KOTA JAMBI - Ruslan Abdul Gani (Jurnal Ilmiah Universitas Batanghari Jambi, 2016)
This research aims to examine the response to the abuse of narcotic drugs by law enforcement and religious awareness in the city of Jambi, with the focus of the study of how law enforcement against abuse of narcotics in the town of Jambi and how religious awareness can help in the prevention of the abuse of narcotics in the town of Jambi. The results showed the efforts of countermeasures against the abuse of narcotic drugs through law enforcement hasn't been fullest do, to overcome countermeasures against abuse of narcotics in the town of Jambi, the recommendation can be given i.e., expected future religion can be portrayed in a manner instilled the values of religious awareness to the community or law enforcement related.Keywords: tackling the Narcotics and Religious Consciousness